The effects of resource extraction on Inuit women and their families: evidence from Canada. Issue 3 (2nd September 2017) - Nightingale, Elana; Czyzewski, Karina; Tester, Frank; Aaruaq, Nadia
ABSTRACT: This article presents the findings from research conducted by Pauktuutit, an Inuit women's organisation, and the University of British Colombia into the gendered social impacts of resource extraction in Qamani'tuaq, Nunavut Territory, Canada. The research used a range of different methods and contributes to a growing body of global evidence on the social impacts of resource extraction on indigenous women and families. It reveals the complex effects of resource extraction on Inuit women's lives, at the individual, family, and community levels. This kind of research is urgently required to ensure that policies on natural resource extraction are developed that support the interests and needs of the women, men, and children most affected by mining.